Foot joint coupling variability differences between habitual rearfoot and forefoot runners prior to and following an exhaustive run - Seneli, R. M.; Beschorner, E.; O'Connor, K. M.; Keenan, K. G.; Earl-Boehm, J. E.; Cobb, S. C. (Journal of Electromyography and Kinesiology, 2021)
As joint coupling variability has been associated with running-related lower extremity injury, the purpose of this study was to identify how variability within the foot may be different between forefoot (FFS) and rearfoot strike (RFS) runners. Identifying typical variability in uninjured runners may contribute to understanding of ideal coordination associated with running foot strike patterns.